2017
DOI: 10.1002/qua.25513
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting geometric preferences in π‐stacking interactions through molecular orbital analysis

Abstract: The preference of π‐stacking interactions for parallel‐displaced (PD) and twisted (TW) conformations over the fully eclipsed sandwich (S) in small π‐stacked dimers of benzene, pyridine, pyrimidine, 1,3,5‐trifluorobenzene, and hexafluorobenzene are examined in terms of enhancement of the inter‐ring density through mixing of the monomer orbitals (MOs). PD and/or TW conformations are consistent with a non‐zero “stack bond order” (SBO), defined in analogy to the bond order of conventional MO theory, as the differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 67 publications
0
18
0
Order By: Relevance
“…This means that: (i) a folded dyad conformer with a p-stacked structure is formed, where the protons of one SBQ unit are in the shielding region of the aromatic nuclei of the neighbouring SBQ unit; (ii) the p-stacked conformer has an asymmetric parallel-displaced structure rather than a symmetrical sandwich structure. 28 Comparison of the fluorescence spectra of the dyad and the model styrylbenzoquinoline indicates the interaction of the two SBQ units in the dyad also in the excited (S 1 ) state. The model styrylbenzoquinoline M1 emits in the violet and blue regions (the emission band maximum is l fl = 424 nm, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that: (i) a folded dyad conformer with a p-stacked structure is formed, where the protons of one SBQ unit are in the shielding region of the aromatic nuclei of the neighbouring SBQ unit; (ii) the p-stacked conformer has an asymmetric parallel-displaced structure rather than a symmetrical sandwich structure. 28 Comparison of the fluorescence spectra of the dyad and the model styrylbenzoquinoline indicates the interaction of the two SBQ units in the dyad also in the excited (S 1 ) state. The model styrylbenzoquinoline M1 emits in the violet and blue regions (the emission band maximum is l fl = 424 nm, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This means that: (i) a folded dyad conformer with a π-stacked structure is formed, where the protons of one SBQ unit are in the shielding region of the aromatic nuclei of the neighbouring SBQ unit; (ii) the π-stacked conformer has an asymmetric parallel-displaced structure rather than a symmetrical sandwich structure. 28…”
Section: Resultsmentioning
confidence: 99%
“…Unlike the bis­(CO) or bis­( t BuNC) adducts of 1 , however, in which the two sp 2 boron moieties are orthogonal to each other, the planes of the two borylene moieties in 4 form an angle of only 52°. As a result, the two IMe Me rings adopt a parallel, staggered conformation with inter-ring distances (2.990(2)–3.418 Å, see Figure S20 in the Supporting Information) typical of π-stacking interactions . Furthermore, unlike in compounds 2 and 3 , the Dip substituents of the cAAC ligands in 4 flank the adjacent IMe Me ligands (Figures and S20).…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the two IMe Me rings adopt a parallel, staggered conformation with inter-ring distances (2.990(2)− 3.418 Å, see Figure S20 in the Supporting Information) typical of π-stacking interactions. 23 Furthermore, unlike in compounds 2 and 3, the Dip substituents of the cAAC ligands in 4 flank the adjacent IMe Me ligands (Figures 3 and S20). This ligand arrangement results in considerable steric strain, which leads to an unusually long B−B bond length of 1.804(2) Å.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…However, SAPT finds E el to be negative (attractive) for such structures due to the charge-penetration effect. [21][22][23] Furthermore, Stone [24] as well as Hill and Legon [10] showed that the characteristic preference of halogen bonding for a linear arrangement is due to exchange-repulsion while the electrostatic contribution is not much affected when a halogen bond is bent. Exchange-repulsion has been found to significantly affect intermolecular interactions in several other cases: Van der Lubbe and Fonseca Guerra concluded that the hydrogen bond in guanine-guanine is stronger than the cytosine-cytosine counterpart due to exchange-repulsion.…”
mentioning
confidence: 99%